Taking the pulse of Mars via dating of a plume-fed volcano - Benjamin E. Cohen (Nature Portfolio, 2017)
Mars hosts the solar system’s largest volcanoes, but their formation rates remain poorly constrained. Here, the authors have measured the crystallization and ejection ages of meteorites from a Martian volcano and find that its growth rate was much slower than analogous volcanoes on Earth.